PERAN GURU DALAM MEMBANGUNAN PENDIDIKAN BERKESADARAN MULTIKULTURAL DI INDONESIA - Masamah, Ulfa; Zamhari, Muhammad (Pascasarjana IAIN Kudus, 2016)
Various multidimensional crises that exist in Indonesia, recognized or not they are the part of the cultural problem which is one of the reasons is the diversity of the cultures that existed in society. The diversity of culture should not be the cause of the existence of discrimination, injustice, suspicion and a variety of human rights violations, but being the power to build a sense of community. Build awareness as above is not easy; it should be with an earnest effort and continuous improvement. One thing that can be done to encourage multicultural awareness is through education. Based on the foregoing, the purpose of this research is to find out how the role of the teacher in developing education with multicultural awareness in Indonesia. This research is a library research is which the data collection was done by gathering the data from a variety of literature. The results showed that in the aspect of education, thinking of multiculturalism should be break down in a variety of important terms that become a strong supporter in promoting diversity that exists in Indonesia. With the implementation of multicultural education, teachers are expected to able to encourage learners to have an awareness and understanding to always uphold the values of Justice, democracy, humanity and pluralism in the association in the middle of our national reality that is full of diversity. There are three important things that must be done by the teacher to build an education with multicultural awareness they are: build an attitude of equality, support the substantial democracy, and build gender awareness.